PENGARUH MODEL PEMBELAJARAN GAMES BASED LEARNING ( GBL) BERBANTUAN APLIKASI WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SDN 26 RIMBO KALUANG - Elsi Afifah; Abna Hidayati; Nofri Hendri; Rahmi Pratiwi (STKIP Subang, 2025)
This study aims to determine the effect of the Games Based Learning (GBL) learning model assisted by the Wordwall application on student learning outcomes in Natural and Social Sciences (NaSS) class IV SDN 26 Rimbo Kaluang, found problems such as low student learning outcomes that have not reached KKTP 75, the learning model is still not varied which makes the learning atmosphere seem boring, less attractive to students so that learning has not been achieved optimally. Learning is still centered on educators, it can be seen that educators dominate learning activities, so that students are less involved in finding contextual problems that are being studied. This type of research is quantitative research using the Quasy Experiment approach. The population in the study were fourth grade students of SDN 26 Rimbo Kaluang. The sampling technique used Total Sampling technique, where the samples in this study were class IV students. A (Experiment Class) and class IV.B (Control Class), each class consisting of 22 students. Data collection techniques using tests in the form of objective questions as many as 20 items that have been tested for validity. After obtaining data on learning outcomes, normality test and homogeneity test were carried out, then continued with the t-test. The results of this study indicate the average value of students who use the Games Based Learning learning model assisted by a t-test.